Replication Data for: What influences transfer of training in an African agricultural research network? - Muthoni Andriatsitohaina, Rachel (International Center for Tropical Agriculture, 2016)
Purpose: A study was conducted to determine the extent to which transfer of training back to work among trainees from national partners of an international bean research network in Africa was perceived to have taken place; and to determine the factors that predicted transfer of training back to the job. Methodology/approach: Online data collection using the Learning Transfer Systems Inventory (LTSI) from 139 respondents was made and analyzed using bivariate correlations and hierarchical multiple regression. Findings: An average of 75% of the training skills were perceived as transferred. Personal capacity significantly predicted transfer, while motivation to transfer, transfer design, supervisor and peer support positively correlated with training transfer. Theoretical implications: The Learning Transfer System Inventory factors remain relevant explanations for training transfer with in African agricultural research and development organizations. Certain work environments are likely to have new factors such as ‘Peer and supervisor’ support which operated as one explanatory factor for training transfer, showing the closeness of peers and supervisors in agricultural research and development settings. Practical implications: The international agricultural research network needs to pay attention to the trainees’ ability to transfer new training, particularly on workload related hindrances. Originality/value: The study has tested out the applicability of the LTSI for international agencies that conduct training for agricultural research and development in Africa. Understanding personal capacity to transfer is critical in this context, suggesting that institutions need policies that enhance trainee capacity to transfer enacted, facilitated and enforced.